Advocacy Journal Club: Teaching Residents and Faculty About Policy and the Importance of Pathology Societies. (11th September 2019) - Talmon, Geoffrey; Wolf, Alejandro; Molani, Mariam; Martin, Kimberly; Jacobs, Jeff; Waibel, Liz
Abstract: Objectives: To describe the Advocacy Journal Club, a novel method to expose pathology residents, fellows, and faculty to critical regulatory and policy issues that affect the practice of laboratory medicine and the importance of involvement in advocacy initiatives. Methods: Six voluntary conferences were held for UNMC faculty, local pathologists, and residents during a 1-year period. Each featured a unique, 50-minute interactive discussion led by a faculty member on a topic related to systems-based practice, public health, and/or legislative reform in health care. The six topics included Stark Law, Medicare Access and CHIP Reauthorization Act of 2015 (MACRA), Laboratory Developed Tests, Executive Branch Influence on Health Care, Local Coverage Determinants, and Protecting Access to Medicare Act of 2014 (PAMA). In addition, all participants completed an 8- to 10-question pre- and posttest. After the completion, a survey to assess the quality and efficacy of the series was administered. Results: Between 5 and 11 residents attended each session. Both residents and faculty demonstrated a marked increase in their posttest scores. In the final survey, 92% stated they gained an understanding of how policy affects their local laboratory and 100% a better appreciation of how involvement in pathology organizations' advocacy efforts impacts the laws, rules, and regulations that affect laboratory medicine. Most (92.3%) reported that topics of the Advocacy Journal Club are important to pathology training and 100% reported that the format was effective. Conclusion: The journal club format is an effective method to teach both residents and faculty about health policy and other issues impacting laboratory medicine and the critical role that participation in the advocacy efforts of pathology societies plays in affecting the future of the specialty.